Socioeconomic drivers of global antimicrobial resistance: a metagenomic analysis - Salehi, Mahkameh (My University, 2024)
Understanding how socioeconomic factors influence the global increase in antimicrobial resistance (AMR) is essential to develop effective public health strategies. In this study, we examined 11,311 human gut microbiome samples derived from metagenomic data across 31 countries. These samples were obtained from the European Nucleotide Archive at the European Institute of Bioinformatics of the European Molecular Biology Laboratory and the Sequence Read Archive at the National Center for Biotechnology information. The metagenomic analysis focused on investigating the presence of antibiotic resistance genes (ARG) within the gut microbiome and understanding population-level AMR trends. To address the challenges in collecting and downloading this extensive dataset, including frequent interruptions in the data retrieval process, an automated pipeline was developed for data acquisition from these databases. The analytical process to download and analyze forward reads from accessions was customized, aligning them with the ResFinder reference database using a k-mer alignment tool kma. Statistical analyzes revealed associations between socioeconomic indicators and ARG load, suggesting that different regions may benefit from tailored approaches to address AMR. This study contributes new methodology and a deeper understanding of the complex interaction between socioeconomic factors and AMR, using metagenomic insights from the human gut microbiome.
Keywords: Antimicrobial resistance (AMR), Human gut microbiome, Big data analytics, Statistical analytics